PERANCANGAN INFOGRAFIS SEBAGAI MEDIA PENGENALAN PROGRAM HOMEVISIT CLEFT CARE INDONESIA - Wira Janitra Gunawan (Universitas Ciputra Surabaya, 2020)
Cleft Care Indonesia is a cleft care foundation that provides free services for the people that needs it. The 2 main services that they provide are educational services to educate the people everything that people need to know about cleft, and free cleft treatment surgeries. Surprisingly, these services that are given away for free are often rejected and ignored by the people. In conducting the research, a qualitative method is used to obtain both the primary and secondary data. After the research was done, it was found that the main cause of the existing on-going problems was the lack of awareness by the people about the foundation Cleft Care Indonesia. One other problem is the cleft stigmas that has been around and told by people for a very long time now, and it is these stigmas that are in the way of people suffering from cleft from seeking medication to treat their cleft. With an informative infographic designed, it is hoped that the design could tell the observers what and who Cleft Care Indonesia is, and briefly explain the Home Visit program ran by the foundation, so that a trust can be formed between the people and the foundation so that people can no longer be afraid to participate and seek medication to treat their cleft. Keywords: free, cleft, medication, campaign